Effects of prior knowledge state assessment and progress assessment on study results in independent learning - Moerkerke, George; Dochy, Filip J.R.C. (Studies in educational evaluation, 1998)
Whether informal subject-oriented prior-knowledge state assessment or information progress-assessment results in increased study pace or a positive effect on final test results was studied with over 9500 open education college students. Student characteristics related to differences in participation in information-assessment procedures were studied with 1081 students. (SLD)